An "Uncrimped" SMart Stapes Prosthesis: A Cause of Late Hearing Deterioration in Otosclerosis. (31st January 2012) - Randhawa, Premjit S.; Hamilton, Nicholas; Narula, Antony A.
Abstract : Statement of Problem . Stapedotomy is the treatment of choice for otosclerosis. Numerous techniques and prosthesis are available to perform this procedure. Success rates of surgery vary from 17% to 80%, and revision surgery carries an increased risk of complications as well as poorer hearing outcomes. Method of Study . Case report. Results . We report the first case of uncrimping of a SMart stapes prosthesis with no lateral displacement as a cause of late failure despite successful crimping and improvement in audiological outcomes after initial surgery. Conclusion . The SMart stapes prosthesis is widely used and has been shown to be safe and provide good hearing outcomes. Displacement of a stapes prosthesis is the commonest cause of failure. Our case shows that deterioration of hearing thresholds can occur from uncrimping of the prosthesis with no displacement. It is important to improve our understanding of stapedotomy failure as revision procedures are associated with poorer outcomes.